Effect of maternal tolerance on behavioral problems in children with enuresis - Mahshameen Munawar; Aasma Yousaf (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the effect of maternal tolerance on behavioral problems in children with enuresis. Method: A cross sectional descriptive study was conducted from January 2018 to November 2018 at three outpatient hospital settings in Pakistan. The sample comprised of 80 mothers (aged 23-50 years) having children with enuresis, who were recruited from one public (tertiary care) and two private (secondary care) outpatient hospital settings in Punjab. Participants were recruited after a formal diagnosis of enuresis made by the consultant pediatrician or psychiatrist. The Tolerance Scale and The Children Behavioural Questionnaire were used to assess maternal tolerance and behavioural problems in children, respectively. A demographics questionnaire with demographic details regarding the mother and the child, was also designed for the study. Results: The mean age of mothers (N=80) and their children was 34.53 ±4.89 years and 8.16 ± 2.36, respectively. Results of correlation analysis revealed that maternal intolerance was positively and significantly correlated with rule-breaking (r=.25, p=.02) and aggressive behaviors (r=.31, p=.01) in children with enuresis. In addition, linear regression analysis was carried out to observe if maternal tolerance significantly contributed to behavioural problems in children with enuresis. Maternal intolerance emerged as significant and positive predictor of rule-breaking behaviors (?=.25, p=.02), aggressive behaviors (?=.31, p=.00) and attention problems (?=.29, p=.01) in the affected children. Conclusion: The study demonstrates that maternal intolerance and hostile attitudes towards children with enuresis leads to secondary behavioural and emotional difficulties. Key Words: Enuresis, Maternal tolerance, Child health care, Continuous...